Disparitas Pandangan Nahwu Abu Bakar Al-Anbari dan Al-Farra’ dalam Kitab “Az-Zāhir Fī Ma’ānī Kalimāti An-Nāsi” Karya Abu Bakar Al-Anbari - Gilang Inggit Maulana Maulana; Mohammad Pribadi; Kholifiatul Masito (Ihtimam : Jurnal Pendidikan Bahasa Arab, 2024)
This article aims to examine and find differences in the views of Nahwu al-Anbari and al-Farra' in the book Az-Zahir by al-Anbari. This type of research is library research with qualitative data and presented descriptively. The data source in this research is the book az-Zāhir Fī Ma'ānī Kalimāti an-Nāsi, as well as several nahwu books related to the research material object. The data collection technique in this research is by note-taking and repeated reading, while the data analysis technique in this research is by qualitative descriptive techniques. The results of the research show that the book az-Zāhir Fī Ma'ānī Kalimāti an-Nāsi by al-Anbari has a tendency to follow the opinion of Basrah ulama on the issue of nahwu. However, in his general Nahwu view, al-Anbari still follows the descriptive Nahwu Kuffah method. Meanwhile, al-Farra' was strict with his Kuffi method. This happened because al-Anbari lived in a newer era so that al-Anbari read more of the views of his predecessor ulama, and al-Farra' lived in an earlier era and still had a ta'asub tendency towards the Kufa method. Keywords: Disparity of Views, Nahwu Kuffah, School of Linguistics